The Birman–Hilden property of covering spaces of nonorientable surfaces - Atalan, F.; Medetogullari, E. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.5 Let p: N → N be a finite covering space of nonorientable surfaces, where χ(N) < 0. We search whether or not p has the Birman–Hilden property.